MADRASAH PRINCIPALS AS EDUCATIONAL SUPERVISORS IN IMPROVING TEACHER PERFORMANC - Zulfi Wahyu Aulia; Nur Effendi; Sulistyorini Sulistyorini (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2026)
The madrasa principal plays a crucial role in improving the quality of learning through educational supervision activities aimed at fostering teacher professionalism. This article aims to analyze the role of the madrasa principal as an educational supervisor in improving teacher performance in madrasas. This study employs a qualitative approach using a library research method. Data were obtained from various scientific literatures, including books, journal articles, and research findings related to educational supervision, madrasa leadership, and teacher performance published within the last five to ten years. The data analysis technique was conducted through three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that educational supervision carried out systematically and continuously by madrasa principals contributes significantly to improving teacher performance. Supervisory activities include supervision planning, classroom observation, feedback provision, and professional guidance through reflective and collaborative discussions. Effective supervision not only functions as an evaluation of teacher performance but also serves as a professional development process that helps teachers improve their pedagogical, professional, social, and personal competencies. Therefore, optimizing the role of the madrasa principal as an educational supervisor is a crucial factor in improving the quality of learning and teacher professionalism in madrasas.